Cinemática de membros inferiores em adolescentes com e sem dor patelofemoral - Foschera, Laura Rossetto (2021)
The etiology of patelofemoral pain (PFP) is multifactorial and some biomechanical aspects of local, distal and proximal origin are highlighted in the literature as potential causes of joint stress in adults, however, it is during adolescence that the onset of symptoms is observed. The investigation of kinematic variables in the adolescent population, especially in functional tasks, has been little explored, making it necessary to analyze the kinematics of the lower limbs of adolescents during a functional test. The aim of this study was to analyze the kinematic pattern of lower limbs during the lateral step test in female adolescents with and without PFP. Kinematic analysis of nine adolescents with patellofemoral pain and nine asymptomatic adolescents was performed during the execution of the Lateral Step Down test. The joint angles of the lower limbs were compared during the execution of the LSD, and the mean values of the hip, knee and ankle angle were interpolated in 101 points for the squat and lift phases. In addition, we used a linear regression model to determine how the hip and ankle angles were related to the frontal knee angles in both groups. There was no statistical difference in the kinematic pattern of the lower limbs during the LSD test between female adolescents with and without PFP. In addition, during the squat and climb phases of the LSD test, coordination between hips, knees and ankles did not differ between groups.